Modeling of CO2-MEA absorption system in the packed column using Sulzer DX structured packing - Shahid, M.Z. (Institute of Physics Publishing, 2020)
The accurate design of a packed column is largely dependent upon the accurate calculation of the effective mass transfer area (ae ) of a packing. The experimental and the modelling study for the packed column with CO2-Monoethanolamine (MEA) system has been reported by employing Sulzer DX packing. The model validation results revealed that the modification in the available simple ae correlations is necessary to attain the reliable results using Sulzer DX packing. Recently, a new simple ae correlation suitable for Sulzer DX packing with MEA-CO2 system has been reported. Therefore, in the present study, the rate-based model is developed using the newly developed ae correlation for the packed absorption column with Sulzer DX structured packing for CO2-MEA system. The model has been successfully validated with the experimental data. Overall results depict good accuracy (AAD < 15) of predicted CO2 concentration profiles due to the reliable ae calculations. However, the relative accuracy is low at high liquid flowrates (> 8 m3/m2h) due to the design limitations of the ae correlation. Therefore, in this study, the adopted ae mass transfer correlation is found suitable for the reliable modelling of the packed absorption column with Sulzer DX packing. Â© Published under licence by IOP Publishing Ltd.